Dorsal inlay inner preputial graft repair versus ventral-only preputial graft repair in primary distal penile hypospadias with narrow urethral plate - Rabea Gomaa Omar; Mostafa M Khalil; Hammouda W Shereef; Mahmoud R Al Ashram; Alaa Elshaer (Urology Annals, 2023)
Background: Tubularized incised plate (TIP) is the most common technique used for distal hypospadias repair with good outcome but with a high rate of urethral stricture. Inner preputial-free graft can be used as an inlay graft in the incised area of the narrow urethral plate, also can be used as an onlay graft for urethroplasty in hypospadias repair to avoid this complication. Patients and Methods: A comparative prospective randomized study was conducted on two groups of hypospadias patients with narrow urethral plate. Group A: dorsal inlay inner preputial graft repair was performed (grafted TIP [G-TIP]) and Group B: ventral onlay preputial graft repair was performed. The assessment of outcome and hypospadias objective scoring evaluation (HOSE) score was done at 2 weeks and 6 months. Results: Group A included 55 patients for whom dorsal inlay inner preputial graft repair was performed (G-TIP), and Group B which was planned to be conducted on 55 patients using onlay preputial graft (onlay graft) but was terminated after 15 cases due to high failure rate (33%). Group A showed better success rate 96% and better HOSE score (score 16) at 2 months and 6 months 83.6% and 88.2% versus 26.7% and 33.3% in Group B. Postoperative complications showed a statistically significant difference; glans dehiscence (3.6% vs. 40%), wound infection (1.8% vs. 33.3%), and skin sloughing (3.6% vs. 26.7%) in Groups A and B, respectively. Conclusion: G-TIP is a good technique for the management of distal hypospadias with narrow urethral plate with good success rate, cosmetic outcome, and with less complications compared to onlay graft.